RANCANG BANGUN CHARGER OTOMATIS PENGONTROL DAYA DAN WAKTU BERBASIS ARDUINO UNO - Mohammad Wahyu Habibulloh; Kurnia Paranita Kartika (Universitas Islam Balitar, 2019)
This final project discusses the design and manufacture of an arduino UNO-based power and time controller automatic charger. On an ordinary charger still does not have a mechanism to cut off the electricity that goes into the charger completely, so researchers have an idea to develop an automatic charger to increase the efficiency of battery charging and to increase the battery life of smartphones. This tool is used to control the charging of a smartphone on the basis of a battery that is used is a capacity of 4100mAH, with the charger used is the Xiaomi 0.35A charger. the remaining percentage of the battery is controlled by using a keypad, the charger will charge the battery in accordance with the time set on each keypad button. The amount of time the battery is charged is displayed on the LCD. When the charging time has finished the relay that is connected to the charger outlet will disconnect the electricity that leads to the charger to stop the charging process and the buzzer will light up as the charging indicator has finished and the LCD will display the words